Utilization of Platform Merdeka Mengajar in the Implementation of Merdeka Curriculum - Pratiwi, Iqmatul; Rahmawati, Desi; Susanto, Teguh Trianung Djoko (Lectura : Jurnal Pendidikan, 2024)
Education has a vital part in improving the nation; if education cannot be regulated, a country would struggle to locate excellent people resources. The higher the quality of an educational institution given by a country's government institutions, the better the standard of living. Previous research explains how to implement a Merdeka curriculum and the characteristics of schools that implement it. This develops project-oriented learning to become more flexible, active, and adaptable. The freedom gives teachers to apply learning methods suitable for students so that the implementation of learning and educational activities is fun, in-depth, and independent. This research aims at providing an overview of the utilization of the Platform Merdeka Mengajar (PMM) in implementing the Merdeka curriculum used in each school that is ready to implement it to determine the impact of the application in empowering all teachers in Indonesia to continue learning and developing their potential. This research was qualitative research with a literature study using descriptive methods. The instrument used documentation, analyzing several journals (research), books, and videos related to the Merdeka curriculum. The result showed that the utilization of the Platform Merdeka Mengajar (PMM) in implementing a Merdeka curriculum with the Indonesia State’s efforts to create a quality educational climate to produce a generation of Pancasila students that the needs and characteristics of students. In conclusion, Merdeka Belajar education, the education system, and its development must align with the educational trends of the 4.0 revolution era.